Monitoring of ecological security patterns based on long-term land use changes in Langsa Bay, Indonesia - Jiaojie Zhang; Fengqin Yan; Vincent Lyne; Xuege Wang; Fenzhen Su; Qian Cao; Bin He (International Journal of Digital Earth)
Southeast Asian coastal zone boasts a concentration of land and marine resources with vulnerable habitats, especially in highly artificial bays. Yet systematic studies on their ecological security assessment are lacking. To investigate the dynamic relationship between land use and ecological security patterns (ESP) in Langsa Bay, we assessed the ESPs for 2002–2023 and four scenarios for 2030 by satellite remote-sensing time series images. We coupled the RF-GLCM algorithm and the InVEST-PLUS model to simulate ecological services. Realizing the ESP construction and relationship dynamics analysis by circuit theory model and ecological security index (ESI) evaluation system. The approach improves the identification of ecological sources, corridors and nodes, providing an explicit spatial framework for conservation prioritization. Results showed that land-use changes strongly influenced ESP, with a 37.55 km2 increase in construction and a 159.78 km2 decrease in forest. Orchards increased by 201.79 km2, leading to a drastic decrease in forest and cropland. Future scenarios suggested that ecological and cropland protections (ESI: 4.56 and 1.98) enhance ecological security, whereas economic development (ESI: −1.20) reduces it. The findings emphasize prioritizing ecological and agricultural land preservation to mitigate ecological risks in bays, offering spatial, temporal and land-use insights for sustainable coastal management.